The pharmacokinetic effect of adalimumab on thiopurine metabolism in Crohn's disease patients. (1st February 2014) - Wong, D.R.; Pierik, M.; Seinen, M.L.; van Bodegraven, A.A.; Gilissen, L.P.L.; Bus, P.; Bakker, J.A.; Masclee, A.A.M.; Neef, C.; Engels, L.G.J.B.; Hooymans, P.M.
Abstract: Background and aims: A drug interaction between infliximab and azathioprine has previously been reported in Crohn's disease patients: the concentration of the main active thiopurine metabolites, the 6-thioguanine nucleotides (6-TGN), increased 1–3 weeks after the first infliximab infusion by 50% compared to baseline. The aim of this prospective study was to determine the effect of adalimumab on thiopurine metabolism in Crohn's disease patients, evaluated by 6-TGN and 6-methylmercaptopurine ribonucleotides (6-MMPR) concentration measurement. Methods: Crohn's disease patients on azathioprine or mercaptopurine maintenance therapy starting with concomitant adalimumab treatment were included. 6-TGN and 6-MMPR concentrations were determined before initiation of adalimumab and after 2, 4, 6 and 12 weeks of combination therapy. The activity of three essential enzymes involving thiopurine metabolism, thiopurine S-methyltransferase (TPMT), hypoxanthine-guanine phosphoribosyl transferase (HGPRT) and inosine-triphosphate pyrophosphatase (ITPase), was evaluated at baseline and week 4. Clinical outcome was evaluated by the Crohn's disease activity index and C-reactive protein concentrations at baseline, week 4 and week 12. Results: Twelve Crohn's disease patients were analyzed. During the follow-up period of 12 weeks the median 6-TGN and 6-MMPR concentrations did not significantly change compared to baseline. TPMT, ITPase and HGPRT enzyme activity did not change either after 4 weeks. In two patients (17%) myelotoxicity was observed within 2–4 weeks, in whom both low therapeutic 6-TGN and 6-MMPR concentrations were found. Conclusions: In this study in Crohn's disease patients no pharmacokinetic interaction was shown between adalimumab and the conventional thiopurines, azathioprine and mercaptopurine.